PENGARUH WORK-LIFE BALANCE DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA BOJONEGORO - Naililmuna Jihan Nabilah; Setiani (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aimed to examine and analyze the effect of employee performance on work-life balance, work environment, and job satisfaction, as well as to test and analyze work-life balance, and work environment on employee performance as a mediating role for job satisfaction. This study uses quantitative research methods with explanatory research. The sample is 41 employees of the Tax Service Office (KPP) Pratama Bojonegoro, with the path analysis method. The results show that: 1. Work-life balance has a positive and significant effect on employee performance, 2. The work environment has a positive and significant impact on employee performance, 3. Work-life balance has a positive and significant impact on employee performance when mediated by job satisfaction. , 4. work environment has a positive and significant effect on employee performance when mediated by job satisfaction, 5. Job satisfaction has a positive and significant effect on employee performance. Keywords: Employee Performance, Work-Life Balance, Work Environment, Job Satisfaction